2010
DOI: 10.1590/s0103-21002010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos, atitudes e práticas acerca da detecção do câncer de próstata

Abstract: Purpose: To describe the knowledge, attitudes, and practice regarding the detection of prostate cancer among men aged between 50 and 80 years old attending a PSF of the municipal district of Juiz de Fora, MG. Methods: This was a cross-sectional home survey with a randomized sample of 160 men residents in the subscript of the program. Results: The majority of participants was married (69.4%), had children (88.8%), used the PSF (86.3%), and had knowledge about detection of prostate cancer. Great number of them h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
27

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
0
5
0
27
Order By: Relevance
“…To do this, there was set up to NiAMHP, which directed the focus of attention of professionals to the most common disorders in the male population, especially in relation to prostate cancer. This disease is the sixth most common malignancy in the world in number of new cases, the third most common cancer in the male population and more neoplasia presented by european men, American and some parts of Africa [3,6,8,10].…”
Section: Discussionmentioning
confidence: 99%
“…To do this, there was set up to NiAMHP, which directed the focus of attention of professionals to the most common disorders in the male population, especially in relation to prostate cancer. This disease is the sixth most common malignancy in the world in number of new cases, the third most common cancer in the male population and more neoplasia presented by european men, American and some parts of Africa [3,6,8,10].…”
Section: Discussionmentioning
confidence: 99%
“…A população deste estudo se enquadrou nesta faixa etária de risco. O predomínio de homens portadores desta doença que se declararam brancos é semelhante a estudos brasileiros que identificaram também o predomínio de homens brancos (11,19) . Contudo, estes dados divergem das estatísticas mundiais, que apontam predominância em indivíduos da raça negra (1,20) .…”
Section: Discussionunclassified
“…Similar data were described in a prior study (10) in which the sample's age ranged between 18 and 81 years, with a mean age of 43 years. It has been reported that early age is an important factor in diagnosing an inherited predisposition to cancer (16)(17) . Hence, health-related efforts to prevent tumors should be encouraged among individuals at an early age, and especially in those people with a family history of malignant tumors (18) .…”
Section: Discussionmentioning
confidence: 99%